Entanglement of humpback whales in artisanal fishing gear in Ecuador - Félix, Fernando; Muñoz, Mercedez; Falconí, Jéssica; Botero, Natalia; Haase, Ben (J. Cetacean Res. Manage., 2020)
Southeastern Pacific humpback whales (Breeding Stock G) congregate along the northwest coast of South America during the austral winter (July– October). Information collected from stranded animals for more than a decade in Ecuador and Colombia indicates that entanglement in fishing gear is a major threat for this population during the breeding season. Twelve new cases are reported here of live individual whales entangled in artisanal gillnets on the central coast of Ecuador from 2004 to 2007. The varying severity of the entanglement and the behaviour of the animals involved indicated that they had differing chances of survival. The findings confirm that the problem persists, although the impact on the population is unknown. The necessity of taking conservation measures to reduce the current level of entanglement is reiterated. Creation and training of rescue teams seems an appropriate alternative in the short-term, but in the long-term it will be necessary to design and implement actions with a wider regional scope, since the problem extends also to at least other two neighbouring countries.